The Effectiveness of Using Busuu Application to Improve Students’ Pronunciation Ability at Grade VIII of SMP Negeri 10 Tapung - Balqis Athiyya; Prih Febtiningsih; Bazilah Raihan Mat Shawal (CV. Rayyan Dwi Bharata, 2026)
This study aims to improve the English pronunciation skills of grade VIII students at SMP Negeri 10 Tapung by utilizing the Busuu application. The research specifically focuses on addressing pronunciation difficulties faced by students, particularly in terms of sounds, stress, intonation, and constructive feedback, through the use of digital media. The research used a quasi-experimental design with two groups: an experimental group using the Busuu application and a control group receiving conventional teaching methods. The study involved 60 students from two classes at SMP Negeri 10 Tapung. Data were collected through pre-tests and post-tests, which assessed students' pronunciation abilities. The experimental group received treatment via the Busuu app, which offers interactive features such as native speaker audio and pronunciation feedback. Statistical analyses, including normality testing, homogeneity testing, and hypothesis testing (paired sample t-test), were performed to determine the effectiveness of the intervention. The study found a significant improvement in the experimental group’s pronunciation skills. The average score of the experimental group increased from 47.7 in the pre-test to 80.2 in the post-test, marking a 32.5-point increase. In comparison, the control group’s score increased from 45.9 to 74.3, a 28.4-point increase. Statistical analysis confirmed the significant effect of the Busuu application on students' pronunciation (p-value = 0.000), supporting the hypothesis that the application enhances pronunciation abilities more effectively than conventional methods. The findings suggest that the Busuu application is an effective tool for improving English pronunciation skills, highlighting the potential of digital media in language learning. The study encourages the integration of interactive and technological solutions in teaching, particularly for overcoming challenges in pronunciation and providing immediate, constructive feedback. However, limitations of the study include the small sample size and the potential influence of external factors not controlled during the experiment. Future research could explore long-term impacts and compare different digital tools for language learning. Additionally, expanding the sample size could provide more generalized results.